VD_FINDINFO HC / 2011 / 615 vom 10. November 2011 - VD Tribunal cantonal (2011)
DÉTENTION AUX FINS D'EXPULSION, MESURE DE CONTRAINTEDROIT DES ÉTRANGERS | 80 al. 5 LEtr, 80 al. 6 LEtr, 20 LVLEtr, 30 LVLEtr